Microalgae separation through silicaaided-sedimentation method for fishpond water treatment and biofuel production - Tan, Kor Yin (2021)
In this research, the silica microparticles is used to harvest microalgae to avoid nanotoxicity. Silica-aided-sedimentation (SAS) method is proposed and carried out through embedding-flocculation and immobilized-on strategies respectively. In embedding-flocculation strategy, at optimum dosage of chitosan and poly(diallyldimethylammonium chloride) (PDDA), 7 mg/L respectively, with 1 g/L of silica, the optimum cell separation efficiencies are achieved at approximately 100 % respectively and the sedimentation rate are 557.21 cm/h and 19.35 cm/h respectively. The chitosan flocculation is mainly driven by bridging mechanism A which formed bigger flocs and led to faster sedimentation. In immobilized-on strategy, the cell separation efficiencies up to 99.89 ± 0.22 % and 99.61 ± 0.16 % are achieved by 1 g/L of chitosan- and PDDA-coated silica respectively. The flocs formed by the chitosan-coated silica are much larger which led to the faster sedimentation rate (501.48 cm/h) compared to PDDA-coated silica (15.38 cm/h). The embedding-flocculation strategy promoted by chitosan is preferably chosen due to the high separation efficiency and sedimentation rate. The silica microparticles is found not toxic to the microalgae, as study model, as the cell density, total lipid, carbohydrate and protein contents of microalgae have no significant changes after 7 days of cultivation with the presence of silica. Furthermore, it promoted cell separation efficiency and sedimentation rate up to 99.78 ± 0.76 % and 324.95 cm/h respectively at 1 g/L of silica with 2 mg/L of chitosan and able to polish the fishpond wastewater by removing 95.45 % of ammoniacal nitrogen, 95.60 ± 1.90 % of nitrate, 94.76 ± 2.42 % of ortho-phosphate, 98.61 ± 0.33 % of turbidity, 98.75 ± 1.77 % of biochemical oxygen demand (BOD), 81.04 ± 0.90 % of chemical oxygen demand (COD), and 36.36 % of total suspended solid (TSS) from the fishpond wastewater. Moreover, around 60 % of unsaturated fatty acids (UFA) which is suitable for the generation of biofuel is successfully extracted from the microalgae by the SAS method through embedding-flocculation strategy. This strategy did not affect the composition of fatty acid from microalgae biomass also proving the reliability for biodiesel production purpose.